Fecal Bacterial Community of Allopatric Przewalski’s Gazelles and Their Sympatric Relatives - Liu, Ruoshuang; Shi, Jianbin; Shultz, Susanne; Guo, Dongsheng; Liu, Dingzhen (Frontiers in Microbiology, 2021)
Mammal gastrointestinal tracts harbor diverse bacterial communities that play important roles in digestion, development, behavior and immune function. Although there is an increasing understanding of the factors that affect microbial community composition in laboratory populations, the impact of environment and host community composition on microbiomes in wild populations is less understood. Given that the composition of bacterial communities can be shaped by ecological factors, particularly exposure to the microbiome of other individuals, inter-specific interactions should impact on microbiome community composition. Here we evaluated inter-population and inter-specific similarity in the fecal microbiota of Przewalski’s gazelle (Procapra przewalskii), an endangered endemic ruminant around Qinghai Lake in China. We compared the fecal bacterial communities of three Przewalski’s gazelle populations, with those of two sympatric ruminants, Tibetan gazelle (P. picticaudata) and Tibetan sheep (Ovis aries). The fecal bacterial community richness (Chao1, ACE) did not vary across the three Przewalski’s gazelle populations, nor did the composition vary between species. In contrast, the managed Przewalski’s gazelle population had higher bacterial diversity (Shannon and Simpson) and was more similar to its sympatric Tibetan sheep in beta diversity than the wild Przewalski’s gazelle populations. These results suggest that ecological factors like host community composition or diet affect Przewalski’s gazelle’s gastrointestinal bacterial community. The role of bacterial community composition in maintaining gastrointestinal health should be assessed to improve conservation management of endangered Przewalski’s gazelle. More broadly, captive breeding and reintroduction efforts may be impeded where captive management results in dysbiosis and introduction of pathogenic bacteria. In free ranging populations where wildlife and livestock co-occur, infection by domestic pathogens and diseases may be an underappreciated threat to wild animals.